Changes in the rheological properties of blood in combat sports athletes (boxing vs MMA) - Aneta Teległów; Łukasz Rydzik; Wojciech Wąsacz; Piotr Snopkowski; Pavel Ruzbarsky; Wacław Mirek; Elżbieta Mirek; Tadeusz Ambroży (Scientific Reports)
Abstract Physical exertion causes significant changes in the rheological properties of blood. Combat sports require athletes to engage in dynamic bouts based on direct confrontation. The aim of this study was to compare the rheological properties of blood before and after confrontation (simulated sparring) in combat sports athletes (Boxing vs MMA) and to compare these with a control group of non-training individuals. The study was conducted on a population of 32 combat sports athletes: 82.06 ± 10.22 kg; 177.41 ± 6.74 cm; BMI 26.03 ± 2.61; age 29.35 ± 5.74 years; training experience 9.47 ± 3.14 years (Boxers group n = 16; MMA group n = 16), all of whom exhibited a high level of athletic performance with regular competition participation. Simulated sparring sessions were conducted, and blood samples were taken before and after the intervention. The blood parameter results were also compared with a control group: 86.97 ± 9.47 kg; 177.31 ± 6.91 cm; BMI 27.64 ± 2.39; age 29.65 ± 5.68 years. In the study, comparing the Boxers pre vs. control group and Boxers post vs. control group showed an increase in elongation index at shear stress 4.24, 8.23, 15.95, 30.94, and 60.00 Pa and a decrease in EI at shear stress 0.58, along with an increase in fibrinogen. For blood morphology indices in the Boxers group compared to the control group, there was an increase in MCV, RDW, WBC, LYM, MON, GRA, PCT, and MPV, with higher values noted for Boxers, and a decrease in MCHC and PDW. Similar trends were observed in blood morphology indices when comparing Boxers pre vs. Boxers post simulated sparring. There was an increase in WBC, LYM, MON, PLT, and PCT after simulated sparring and a decrease in EI at shear stress 2.19. Analyzing the results comparing MMA pre vs. control group and MMA post vs. control group, higher values were observed in the MMA group for MCV, WBC, LYM, GRA, PCT, EI at shear stress 30.94 and 60.00, and fibrinogen. Conversely, in the MMA pre vs. control group and MMA post vs. control group, lower values were found for EI at shear stress 0.58 and 1.13. Comparing MMA pre vs. MMA post fight, blood morphology indices were significantly higher in athletes after simulated sparring, with a significant increase in AI after intervention. MMA fights are often longer and more intense than boxing matches, which in turn affects the rheological properties of blood. This is confirmed by the results showing a decrease in red blood cell deformability in the MMA group compared to Boxers, with no changes in AI, AMP, T1/2, blood plasma viscosity, and fibrinogen. The rheological indices of blood indicate that MMA fights have a more negative impact on blood flow compared to boxing matches.